Professional Learning Development for Classroom Action Research in Entrepreneurship Subjects in Indonesia - Abdi Darmawan; S. Sicat, Alvin (Moneter: Jurnal Keuangan dan Perbankan, 2025)
The study adopted an Action Research (AR) framework in devising professional learning strategies that help improve the learning advancement among entrepreneurship teachers in Indonesia in enhancing the effectiveness of learning and students' engagement. The study was iterative: data was collected through cyclical phases of planning, action, observation, and reflection and was carried out with 15 educators at 5 high schools. We integrated Project-Based Learning (PBL) instructional practices and more use of digital tools. We administer pre- and post-intervention surveys, conduct classroom observations, and assess student performance. The results were significant improvements in teacher competencies, with post-intervention scores increasing by up to 30.77%, and student engagement increased from 68% to 85%. The study concludes that AR-based development strengthens entrepreneurship teaching, enhances student-centered learning, and offers a scalable, effective model for educational innovation in resource-limited environments.